“The Cure” in Margary’s The Postmortal: A Vanishing Technological and Transhumanist Mediator Towards an Ageless Existence - Niñoval Pacaol (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The 2011 science fiction novel of Drew Magary named The Postmortal drew a world wherein the cure for aging has been scientifically and technologically advanced through gene therapy by the medical practitioner Graham Otto. This paper hinges on the ‘vanishing mediator’ as a theoretical framework synthesized by Kahambing which runs in four distinct stages for its entire process, namely, to: a.) retroactively trace the intervention, b.) evaluate the intervention, c.) identify the mediator, and d.) locate the vanishing point. Applying this to the movement, the methodological structure of the paper is divided into four parts. First, it provides a primary discussion of the social “normal” condition of people in the novel to traceably locate the intervention made by Graham Otto, a doctor, to completely halt the aging process. Second, the researcher presented a technological intervention of gene therapy in the character of Doctor Otto in making a scientific cure for aging. Third, the said intervention is argued to be a vanishing mediator. Finally, it gave a full account of the major implications of a Bostromean transhuman process and its traces in the world at large.